The Changing Roles Of Trade Unions In India: A Case Study Of National Thermal Power Corporation (Ntpc), Unchahar - Ghosh, Piyali; Nandan, Shefali; Gupta, Ashish (Asian Academy of Management (AAM), 2009)
Trade unions are a major component of the system of modern industrial relations in any nation, each having, in their constitution, their own set of objectives or goals to achieve. Change in the political, social and educational environment has seen them rechristened as a forum that protects and furthers workers' interests and improves the quality of life of workers, enlarging their traditional roles of establishing terms and conditions of employment. This paper focuses on plant level trade unions, particularly those of the National Thermal Power Corporation (NTPC) Unchahar plant, one of the largest and best Public Sector Undertakings of India. This exploratory study of the different trade unions operational at the Unchahar plant will also highlight their ideologies, objectives and structures. We aim to capture the changing paradigms in the roles of plant-level unions: from maintaining good industrial relations, once considered their primary role, they now work actively to improve the quality of life of workers, a role earlier considered to be secondary.